Pharmacological Blockade of 5-HT(7) Receptors as a Putative Fast Acting Antidepressant Strategy - Mnie-Filali, Ouissame (Nature Publishing Group, 2011)
Current antidepressants still display unsatisfactory efficacy and a delayed onset of therapeutic action. Here we show that the pharmacological blockade of serotonin 7 (5-HT(7)) receptors produced a faster antidepressant-like response than the commonly prescribed antidepressant fluoxetine. In the rat, the selective 5-HT(7) receptor antagonist SB-269970 counteracted the anxiogenic-like effect of fluoxetine in the open field and exerted an antidepressant-like effect in the forced swim test. In vivo, 5-HT(7) receptors negatively regulate the firing activity of dorsal raphe 5-HT neurons and become desensitized after long-term administration of fluoxetine. In contrast with fluoxetine, a 1-week treatment with SB-269970 did not alter 5-HT firing activity but desensitized cell body 5-HT autoreceptors, enhanced the hippocampal cell proliferation, and counteracted the depressive-like behavior in olfactory bulbectomized rats. Finally, unlike fluoxetine, early-life administration of SB-269970, did not induce anxious/depressive-like behaviors in adulthood. Together, these findings indicate that the 5-HT(7) receptor antagonists may represent a new class of antidepressants with faster therapeutic action.